2022
DOI: 10.3389/fmars.2022.782456
|View full text |Cite
|
Sign up to set email alerts
|

The Extent and Pattern of Mariculture Impacts on Spatial and Seasonal Variations of Sediment Bacterial Communities Among Three Coastal Waters

Abstract: Benthic sediment bacteria are important drivers for material circulation and energy flow in aquatic ecosystem, and they are sensitive to environmental changes. Large scale suspended mariculture in coastal waters induces high organic loading to the sediment through biodeposition, and causes changes in sediment biogeochemical features. However, the impacts of mariculture on sediment bacterial communities are not fully understood. In the present study, sediment samples were collected from three coastal semi-enclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…That is, the archaeal Pielou's evenness showed little spatial difference among three river reaches, while the bacterial Pielou's evenness increased from upstream to downstream. Through the results of the correlation analysis, we found that water temperature was positively correlated with Pielou's evenness of bacteria, but was not correlated with that of archaea, which was consistent with the results of previous studies (Shi et al, 2022; Zhang, Chen, et al, 2021). We speculated that bacterial Pielou's evenness was potentially influenced by water temperature, increasing with water temperature from upstream to downstream.…”
Section: Discussionsupporting
confidence: 91%
“…That is, the archaeal Pielou's evenness showed little spatial difference among three river reaches, while the bacterial Pielou's evenness increased from upstream to downstream. Through the results of the correlation analysis, we found that water temperature was positively correlated with Pielou's evenness of bacteria, but was not correlated with that of archaea, which was consistent with the results of previous studies (Shi et al, 2022; Zhang, Chen, et al, 2021). We speculated that bacterial Pielou's evenness was potentially influenced by water temperature, increasing with water temperature from upstream to downstream.…”
Section: Discussionsupporting
confidence: 91%
“…The PCR amplification primers of bacterial V4-V5 regions were 515F (5′-GTGYCAGCMGCCGCGGTAA-3′) and 926R (5′-CCGYCAATTYMTTTRAGTTT-3′) (Parada et al, 2015). PCR reactions, further processing, and sequencing of PCR products were performed following a method described in Shi et al (2022). In addition, demultiplexed, quality-filtered, and merged methods of raw 16S rRNA gene sequencing reads were described in Shi et al (2022).…”
Section: Dna Extraction Sequencing and Analysismentioning
confidence: 99%
“…PCR reactions, further processing, and sequencing of PCR products were performed following a method described in Shi et al (2022). In addition, demultiplexed, quality-filtered, and merged methods of raw 16S rRNA gene sequencing reads were described in Shi et al (2022). The high-quality sequences were then clustered into operational taxonomic units (OTUs) with 97% similarity using UPARSE (Edgar, 2013), with a minimum number of sequences (27106) as the rarefied criterion to standardize uneven sequence depth.…”
Section: Dna Extraction Sequencing and Analysismentioning
confidence: 99%
“…As primary producers, these prokaryotes form an indispensable foundation of the food web of the ARS ecosystem, supporting a diverse range of benthic life, from microbial consumers to animals like zooplanktons, clams, mussels, and shrimps [13]. Bacterial communities can exhibit spatial or temporal patterns and are influenced by different environmental parameters and human activities [14,15], such as artificial reef construction in marine ranching [16]. In recent decades, a long-standing research focus has been on microbial communities' distribution patterns in marine sediments [17].…”
Section: Introductionmentioning
confidence: 99%